Combinations of physical activity, sedentary time, and sleep duration and their associations with depressive symptoms and other mental health problems in children and adolescents: a systematic review - Hugues Sampasa-Kanyinga; Ian Colman; Gary S. Goldfield; Ian Janssen; JianLi Wang; Irina Podinic; Mark S. Tremblay; Travis J. Saunders; Margaret Sampson; Jean-Philippe Chaput (BMC, 2020)
Abstract Background For optimal health benefits, the Canadian 24-Hour Movement Guidelines for Children and Youth (aged 5-17 years) recommend an achievement of high levels of physical activity (≥60 min of moderate-to-vigorous physical activity), low levels of sedentary behaviour (≤2 h of recreational screen time), and sufficient sleep (9-11 h for children or 8-10 h for adolescents) each day. The objective of this systematic review was to examine how combinations of physical activity, sedentary time, and sleep duration relate to depressive symptoms and other mental health indicators among children and adolescents. Methods Literature was obtained through searching Medline, EMBASE, PsycINFO, and SportDiscus up to September 30, 2019. Peer-reviewed studies published in English or French were included if they met the following criteria: population (apparently healthy children and adolescents with a mean age of 5-17 years), intervention/exposure (combinations of physical activity, sedentary time, and sleep duration), and outcomes (depressive symptoms and other mental health indicators). A risk of bias assessment was completed for all included studies using the methods described in the Cochrane Handbook. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) framework was used to assess the quality of evidence for each health indicator. Narrative syntheses were employed to describe the results due to high levels of heterogeneity across studies. Results A total of 13 cross-sectional studies comprised in 10 papers met inclusion criteria. Data across studies involved 115,540 children and adolescents from 12 countries. Overall, the findings indicated favourable associations between meeting all 3 recommendations and better mental health indicators among children and adolescents when compared with meeting none of the recommendations. There was evidence of a dose-response gradient between an increasing number of recommendations met and better mental health indicators. Meeting the screen time and sleep duration recommendations appeared to be associated with more mental health benefits than meeting the physical activity recommendation. The quality of evidence reviewed was "very low" according to GRADE. Conclusions The findings indicate favourable associations between meeting all 3 movement behaviour recommendations in the 24-h guidelines and better mental health indicators among children and adolescents. There is a clear need for high-quality studies that use robust measures of all movement behaviours and validated measures of mental health to increase our understanding in this topic area.